An exploration of compositional techniques used in Gamelbati – Mediasi ukiran III by Tazul Izan Tajuddin / Nur Syafiqah Shuib - Shuib, Nur Syafiqah (Faculty of Music, 2015)
This research thesis comprises an exploration of compositional techniques encountered in the whole sections of Gamelbati by Dr. Tazul Izan Tajuddin. It is interesting to explore how the basic idea of "weaving" has been transformed into a musical element specifically in Gamelbati - Mediasi Ukiran III In this thesis, I demonstrate that Dr. Tazul successfully mediated between East and West in Gamelbati. My analysis covers the tempo, instrumentation, time signature, textures, pulses, center - internal drone, ornamental notes and extended techniques on the strings on the each sections of Gamelbati. In summary, this research focuses the compositional method used by Dr. Tazul in Gamelbati. The interview session results that the appreciation of art music in Malaysia is still backward and needs development.